The RUB Cage: Respiration–Ultrasonic Vocalizations–Behavior Acquisition Setup for Assessing Emotional Memory in Rats - Hegoburu, Chloe; Shionoya, Kiseko; Garcia, Samuel; Messaoudi, Belkacem; Thevenet, Marc; Mouly, Anne-Marie (Frontiers in Behavioral Neuroscience, 2011)
In animals, emotional memory is classically assessed through pavlovian fear conditioning in which a neutral novel stimulus (conditioned stimulus) is paired with an aversive unconditioned stimulus. After conditioning, the conditioned stimulus elicits a fear response characterized by a wide range of behavioral and physiological responses. Despite the existence of this large repertoire of responses, freezing behavior is often the sole parameter used for quantifying fear response, thus limiting emotional memory appraisal to this unique index. Interestingly, respiratory changes and ultrasonic vocalizations (USV) can occur during fear response, yet very few studies investigated the link between these different parameters and freezing. The aim of the present study was to design an experimental setup allowing the simultaneous recording of Respiration, USV and Behavior (RUB Cage), and the offline synchronization of the collected data for fine-grain second by second analysis. The setup consisted of a customized plethysmograph for respiration monitoring, equipped with a microphone capturing USV, and with four video cameras for behavior recording. In addition, the bottom of the plethysmograph was equipped with a shock-floor allowing foot-shock delivery, and the top received tubing for odor presentations. Using this experimental setup we first described the characteristics of respiration and USV in different behaviors and emotional states. Then we monitored these parameters during contextual fear conditioning and showed that they bring complementary information about the animal’s anxiety state and the strength of aversive memory. The present setup may be valuable in providing a clearer appraisal of the physiological and behavioral changes that occur during acquisition as well as retrieval of emotional memory.